(NsOWREMENNYE FIZI^ESKIE METODY W GEOHIMII (B:s (Nu^EBNOE POSOBIE (B/s - (NbARABANOW(B, (NwLADIMIR fEDOROWI^s; (NgON^AROW(B, (Ng(B.(Nn(B.s; (NzORINA(B, (Nm(B.(Nl(B.s ((NlENINGRAD (B:s (NiZD(B-(NWO lgu(B,s, 1990)
(NbIBLIOGR(B.: (NS(B. 380-383s
(NpREDM(B. (NUKAZ(B.: (NS(B. 384-387s
(NaWT(B. (NUKAZANY NA OBOROTE TIT(B. (NL(B.s
Keywords: (NgEOHIMIQs